The quality of care for type 2 diabetes mellitus management in Malaysian primary health care settings: A scoping review of ABC (glycated haemoglobin A1c, blood pressure, and LDL-cholesterol) - Mohamad Zulfikrie Abas; Norshahiratul Atiqah Mohd Zaidi; Pei Jia Lee; Xin Rou Teh; Kim Sui Wan; Azah Abdul Samad; Huan Keat Chan; Sheamini Sivasampu; Swee Hung Ang (PLoS ONE, 2026)
Background Diabetes is a major health concern in Malaysia, yet no comprehensive review has assessed the quality of care for these patients. This study aims to systematically review published evidence on type 2 diabetes mellitus (T2DM) management in Malaysian primary health care (PHC), focusing on the achievement of glycated haemoglobin (HbA1c), blood pressure (BP), and LDL-cholesterol (LDL-C) targets (ABC control). Methods A scoping review was conducted, involving a comprehensive search of four databases (PubMed, Embase, Scopus, and MyMedR) and grey literature for publications up to December 2024. Studies were included if they reported on at least one ABC indicator among the general adult T2DM population in Malaysian PHC settings. The scoping review followed the Joanna Briggs Institute (JBI) methodology and PRISMA-ScR guidelines. EndNote was used for deduplication, and Rayyan was utilised for the screening process. Data were extracted and synthesised narratively. Results A total of 109 publications were included. Publications increased post-2010 but remained geographically concentrated in urban states. Large-scale studies heavily relied on the National Diabetes Registry. HbA1c was the most reported indicator. Findings revealed no evidence of improvement in HbA1c and BP control over two decades; achievement rates were 30–45% for HbA1c (<7.0%) and 20–50% for combined BP target (<130/80 mmHg). Conversely, LDL-C control (≤2.6 mmol/L) showed a modest improvement, with achievement rates rising from approximately 30% to 50% over a decade. Conclusion Despite a substantial increase in research, the HbA1c and BP control for T2DM in Malaysian PHC has remained static and suboptimal, highlighting a persistent gap between clinical guidelines and real-world outcomes. The modest improvement in LDL-C suggests that progress is achievable. These findings underscore the need for a balanced policy focus on all three ABC indicators, strategies to overcome systemic barriers, and continued investment in the national registry to guide evidence-based improvements in diabetes care.